Introduction to Automata Theory : Languages, and Computation - Hopcroft, John E.; Motwani, Rajeev; Ullman, Jeffrey D. ([S.l.] : Prentice Hall, 2013)
This classic book on formal languages, automata theory, and computational complexity has been updated to present theoretical concepts in a concise and straightforward manner with the increase of hands-on, practical applications. This new edition comes with Gradiance, an online assessment tool developed for computer science. Please note, Gradiance is no longer available with this book, as we no longer support this product.
Keywords: Machine theory; Formal languages; Computational complexity